Analisis Faktor Yang Berhubungan Dengan Kunjungan Antenatal Care (ANC) di Puskesmas Mariana Tahun 2023. - Rika Victoria; Ali Harokan; Gema Asiani (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
Antenatal Care (ANC) is a health service for pregnant women in the months and weeks before birth which aims to develop pregnant women and their fetuses. This study aims to determine the factors of age, parity, occupation, knowledge, attitudes and family support related to Antenatal Care (ANC) visits at the Mariana Health Center in 2023,. The research design is quantitative with a cross sectional approach. The population in this study is pregnant women seeking treatment at Mariana in 2022, which is 16354 respondents. Sampling using slovin theory. The sample in this study amounted to 99 people. How to take samples using purposive sampling. Data collection for this research was carried out from June 05 2023 to June 19 2023. Data collection was carried out using a Likert scale questionnaire. Bivariate data analysis using the Chi-Square test. The results showed that there was a relationship between parity (p value 0.035), knowledge (p value 0.022), family support (p value 0.011) and Antenatal Care (ANC) visits at the Mariana Health Center in 2023. There was no relationship between age (p value 0.801), occupation (p value 0.423) and attitudes (p value 0.190) with Antenatal Care (ANC) visits at the Mariana Health Center in 2023. There is a need for efforts to increase knowledge and motivation for family participation in antenatal care visits.